Native trees on Mount Lantoy key biodiversity areas (KBA), Argao, Cebu, Philippines - Lillo, Edgardo P.; Rosales, Raamah; Nuevo, Ritchie U.; Alcazar, Steve Michael T.; Malaki, Archiebald B. (2019)
The forest cover of Cebu Island was now less than 1% of its total land area. The almost complete deforestation of Cebu Island has apparently led to the extinction of many native trees, birds, and other wildlife. Assessing native trees on Mount Lantoy key biodiversity areas (KBA) was important in providing materials to support the human decision-making process in the management of the area. Permanent plots with 20 m x 100 m dimension were established both in lower and upper elevations of Mount Lantoy KBA. A total of four plots were established in highly stratified vegetation to generate information in all vegetation classes. A total of 112 species, classified into 64 families and 84 genera, were recorded. Out of 112 species, 88 were native trees, 10 shrubs, three ferns, three herbs, four vines, and four epiphytes. Majority of the species were recorded in Plots 1, 2, and 4. Seventeen native trees were categorized as threatened ? with two species considered as critically endangered, three endangered, nine vulnerable, and three other threatened species identified. Mount Lantoy KBA has high species diversity (?H = 3.5?), dominated by the species of Parishia malabog Merr. (15.287%) in terms of diameter, richness, and density per hectare. Majority of the native trees have a diameter of 10?19 cm (66%) and basal area of 8 m2/ha. Native trees of Mount Lantoy were threatened by illegal cutting, hunting, and the rampant conversion of forests to agriculture, with disturbance index value of moderately disturbed. All this information on native trees were essential for decision making, particularly in the rehabilitation and conservation of Mount Lantoy KBA. (Author's abstract)